2011
DOI: 10.1152/ajprenal.00697.2010
|View full text |Cite
|
Sign up to set email alerts
|

Persistent kidney dysfunction in swine renal artery stenosis correlates with outer cortical microvascular remodeling

Abstract: Percutaneous transluminal renal stenting (PTRS) does not consistently improve renal function in patients with atherosclerotic renovascular disease, but the mechanisms underlying irreversible kidney injury have not been fully elucidated. We hypothesized that renal dysfunction after PTRS is linked to ongoing renal microvascular (MV) remodeling. Pigs were studied after 10 wk of atherosclerosis and renal artery stenosis (ARAS), ARAS treated with PTRS 4 wk earlier, and normal controls (n = 10 each). Renal blood flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
87
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

6
4

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 51 publications
(63 reference statements)
7
87
0
Order By: Relevance
“…While small clinical studies have reported significant improvement in blood pressure and renal function among PTRA-treated patients [4,5], large randomized clinical trials failed to determine an incremental value of PTRA, on a top of medical therapy, for the treatment of ARVD [6,7]. In agreement, we have previously shown in a swine model of ARVD that PTRA normalizes blood pressure levels, but fails to improve tubulointerstitial injury, microvascular rarefaction, and renal function in the stenotic kidney [8].…”
mentioning
confidence: 65%
“…While small clinical studies have reported significant improvement in blood pressure and renal function among PTRA-treated patients [4,5], large randomized clinical trials failed to determine an incremental value of PTRA, on a top of medical therapy, for the treatment of ARVD [6,7]. In agreement, we have previously shown in a swine model of ARVD that PTRA normalizes blood pressure levels, but fails to improve tubulointerstitial injury, microvascular rarefaction, and renal function in the stenotic kidney [8].…”
mentioning
confidence: 65%
“…In addition, although the Bland-Altman analysis did not exhibit a consistent bias, lower GFR values might narrow the differences between two methods. Notably, restoring stenotic kidney blood flow after stent placement was not associated with (32). Our methods are limited by the use of central contrast material injection by using a catheter advanced after renal vein sampling.…”
Section: Genitourinary Imaging: Single-kidney Glomerular Filtration Rmentioning
confidence: 96%
“…Partial reversal of these structural and functional changes in the cortical circulation, and increased basal RBF and GFR, is seen after percutaneous transluminal renal artery stenting, to remove the stenosis, at least in a porcine model of RVD uncomplicated by hypercholesterolemia [ 67 ]. However, this treatment is much less effective when RVD is complicated by atherosclerosis [ 65 ]. Thus, renal artery stenosis, particularly when accompanied by hypercholesterolemia, appears to set in train a cascade of events, associated with oxidative stress, fi brosis, infl ammation, apoptosis, vascular remodeling and endothelial dysfunction, which are at best only partially reversible.…”
Section: Renal Perfusion and Glomerular Filtrationmentioning
confidence: 99%